Accounting Attitude Scale: Analisis Perbedaan Sikap Mahasiswa Akuntansi Terhadap Akuntansi (Studi Pada Perguruan Tinggi di Yogyakarta) - Yusti Pujisari; Frasto Biyanto; Bunga Vidyaningrum; Junaidi Affan (Faculty of Economics and Business, Universitas Warmadewa, 2024)
In general, every student in accounting who has just taken accounting education has a positive attitude toward accounting. However, over the course of their study, the attitude is thought to change, both ini a positive and negative direction. This study aims to test whether there are differences between senior and junior accounting students in attitude towards accounting as a discipline, accounting as a group activity, accounting as a profession and accounting as a career. The research was conducted using a questionnaire adopted from Accounting Attitudes Scale by Nelson and consisted of 15 question items. Research respondents were students of one university in Yogyakarta, which consisted of first semester students (junior students) and final semester students (senior students). Total respondents obtained were 161 respondents. The research results from testing using Mann Whitney test showed that there was significantly difference in the attitude toward accounting as a discipline, accounting as a group activities, accounting as a profession and accounting as a career between yunior and senior students. The overall results of the hypothesis also show that the attitude scores of senior students are lower than those of junior students. This indicates a decrease in positive attitudes along with experience in learning accounting at the university